2011
DOI: 10.1002/chem.201101062
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐Layer Assembly of Na9[EuW10O36]⋅32 H2O and Layered Double Hydroxides Leading to Ordered Ultra‐Thin Films: Cooperative Effect and Orientation Effect

Abstract: Well‐ordered, ultra‐thin films (UTFs) based on the hybrid assembly of Na9[EuW10O36]⋅32 H2O (denoted as EuW10) and exfoliated MgAl layered double hydroxide (LDH) monolayers have been fabricated by utilising a layer‐by‐layer (LBL) technique. The assembly process was monitored by UV/Vis absorption and fluorescence spectroscopy measurements to get a stepwise and regular growth of the UTFs upon increasing the deposited cycles. In the resulting (EuW10/LDH)n UTFs, the intercalation of EuW10 anions into LDH monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 84 publications
1
24
0
Order By: Relevance
“…The thin films display uniform bright red or green luminescence with increasing intensity from 30 to 75 (or 20 to 80) bilayers. No clear red‐ or blue‐shift of the absorption and emission spectra for the (Eu(DPA) 3 3− /LDH) n and (Tb(DPA) 3 3− /LDH) n UTFs with a different number of bilayers were observed, which suggests that no intermolecular interactions between Eu(DPA) 3 3− or Tb(DPA) 3 3− clusters in the neighbouring layers were formed during the assembly process …”
Section: Resultsmentioning
confidence: 97%
“…The thin films display uniform bright red or green luminescence with increasing intensity from 30 to 75 (or 20 to 80) bilayers. No clear red‐ or blue‐shift of the absorption and emission spectra for the (Eu(DPA) 3 3− /LDH) n and (Tb(DPA) 3 3− /LDH) n UTFs with a different number of bilayers were observed, which suggests that no intermolecular interactions between Eu(DPA) 3 3− or Tb(DPA) 3 3− clusters in the neighbouring layers were formed during the assembly process …”
Section: Resultsmentioning
confidence: 97%
“…Various photoresponsive LDH LbL‐multilayer films containing photoactive molecules or complexes have also been described, involving for instance poly(1‐4[4‐(3‐carboxy‐4‐hydroxyphenylazo) benzenesulfonamido]‐1,2‐ethanediyl sodium salt), 1,3,6,8‐pyrenetetrasulfonic acid, Na 9 [EuW 10 O 36 ], 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonate), hydroxide/8‐amino‐1,3,6‐naphthalenetrisulfonate, calcein, spiropyran, luminol, and erythrosine B . Such a self‐assembly approach via electrostatic interactions was further adapted to coimmobilize two types of anionic dye molecules, i.e., tetrakis(4‐carboxyphenyl)porphyrin or perylene 3,4,9,10‐tetracarboxylate with polymer anions such as poly 4‐styrene sulfonate and poly vinyl sulfonate .…”
Section: New Trends and Strategies For Ldh And Hybrid Ldh Synthesismentioning
confidence: 99%
“…Inversely, it was found that acidic AAs quench the luminescence while nonpolar AAs do not significantly influence the optical properties of the POM (Zhang et al, 2016 ). The processing of EuW 10 by incorporation into films has been achieved, allowing the fabrication of moisture-responsive systems (Clemente-León et al, 2010 ; Xu et al, 2011 ; Qiu et al, 2015 ). Based on all these results, we have undertaken to elaborate a multi-functional hybrid system where the EuW 10 POM is incorporated in the cavities of a metal-organic framework (MOF).…”
Section: Introductionmentioning
confidence: 99%